DAMPAK RITEL MODERN TERHADAP PEDAGANG RITEL TRADISIONAL DI WILAYAH URBAN PROVINSI JAWA TENGAH - Saryadi, Saryadi (JURNAL ILMU SOSIAL, 2014)
At this time a very flourishing modern small-scale retail store open to the urban areas between districts / cities. This phenomenon is beneficial for the community shopper / customers, but considered very detrimental to traditional retailers. The presence of modern retail adjacent to supplement traditional retail competition, because the goods sold relatively the same. The purpose of this study to determine the impact of modern retail presence to traditional retail in Urban Areas in Central Java Province.As the object of this study is the owner of a traditional retail in the urban area of Central Java Province. Sampling area includes traditional retailers located in the Semarang City – Demak District, Demak District – Kudus District, Semarang City- Kendal District, Kendal District – Batang District, Pekalongan City, Batang District, Semarang District- Salatiga City, Salatiga City – Boyolali District, and Semarang District – Temanggung District. Purposively selected sample criteria; contained modern retail ( Indomart / Alfamart , etc. ) within a radius of 2 kilometers from the farthest traditional retail and traditional retail establishment earlier than modern retail, as well as modern retailing began operation after 4 months of time since the survey.Sample size was 100 traditional retail spread in each sampling area. Analysis methods used in this study is a quantitative method, using statistical analysis with a description diskripstif single table. While infrensial statistical analysis used to test different modern retail impact on traditional retail turnover includes sales, merchandise range, the number of buyers. It also conducted a regression analysis to determine variables that could explain some of the impact of modern retail presence in traditional retail.Based on the analysis, traditional retailers feel the impact of the presence of modern retail is located adjacent to the store, namely reduction in sales turnover, reduced profitability, reduced variety of merchandise sold, and the declining number of buyers. While based on different test average gain in sales turnover, merchandise range, and the number of buyers between before and after the introduction of modern retailing, significant differences, the decline in sales turnover, a decrease in the variety and quantity of merchandise, and the number of buyers. Regression test results concluded that the distance does not affect the change in sales turnover in traditional retail stores, and the distance has an influence on the number of buyers at traditional retail stores.Recommendations from this study, which party should have the authority to regulate the permissibility radius modern retail stores operating in the region. Also the modern retail businesses not too much to open retail stores adjacent to the modern traditional retail stores that have been there before.